Development of Teaching Materials Based on Pjbl-Abmh (Preserved Bioplastic Materials Set) To Improve Students' Creative Thinking Skills - Auni, Anggita; Farida, Siti; Arfiansyah, Noval Ilham; Sari, Yurizka Melia (Jurnal Riset Pendidikan dan Inovasi Pembelajaran Matematika, 2024)
This research describes the process and results of developing PJBL-ABMH-based learning tools to improve students' creative thinking abilities on set material. This research uses the Plomp development model to develop learning tools through teaching modules and project worksheets, setting material with the PJBL-ABMH project learning design. The trial was conducted on 6 grade 7 students at a junior high school in Surabaya, East Java. Data collection and analysis techniques are carried out using validation sheets to determine the validity of the learning tools tested on the validator. Pre-test and posttest sheets measure effectiveness regarding students' creative thinking abilities on set material. Apart from that, student response sheets are also used to determine the practicality of the learning tools that have been developed. Data analysis was carried out using the constant comparative method technique. The results of the data analysis showed that the learning tools obtained a validity criterion of 75.5%, and each was classified as valid. The n-gain was obtained at 0.736 for the effectiveness criteria, and each obtained high effectiveness criteria. The learning tools were efficient to implement, with an average student response of 90% for the project learning design. Thus, PJBL-ABMH-based learning tools are declared valid, effective, and practical.